The effects of probiotics, prebiotics, and synbiotics on polycystic ovarian syndrome: an overview of systematic reviews - Angoorani, Pooneh; Ejtahed, Hanieh-Sadat; Ettehad Marvasti, Fateme; Taghavi, MinaSadat; Mohammadpour Ahranjani, Behzad; Hasani-Ranjbar, Shirin; Larijani, Bagher (Frontiers in Medicine, 2023)
Introduction Accumulating evidence has highlighted the critical role of the gut microbiota and its potential action as a regulator of metabolic disorders including insulin resistance, obesity, and systemic inflammation in polycystic ovarian syndrome (PCOS). Microbiota-modulating interventions, such as probiotics, prebiotics, and synbiotics, could be effective in PCOS management. Methods We conducted an overview of systematic reviews (SRs) and meta-analyses to summarize reviews regarding the effectiveness of probiotics/prebiotics/synbiotics on the management of PCOS through a systematic literature search in PubMed, Web of Science, and Scopus databases until September 2021. Results Eight SRs and meta-analyses were included in this study. Our overview confirmed that probiotic supplementation had a potentially beneficial effect on some PCOS-related parameters including body mass index (BMI), fasting plasma glucose (FPG), and lipid profiles. Evidence shows that synbiotics in comparison with probiotics were less effective on these parameters. The methodological quality of SRs was assessed using the AMSTAR-2 assessment tool and was determined as high for four SRs, low for two SRs, and critically low for one SR. Due to limited evidence and high heterogeneity of the studies, it remains difficult to identify optimal probiotics strains, prebiotics types, length of duration, and doses. Discussion Future clinical trials with higher quality are recommended to clarify the efficacy of probiotics/prebiotics/synbiotics on the management of PCOS and provide more accurate evidence.